Oxidative stress, antioxidant capacity, and cardiovascular risk in patients with non-functioning adrenal incidentalomas - Hanife Bolat Erdogan; Kamile Gül; Tuncay Sahutoglu; Volkan Erdogan (Endocrine Connections, 2025)
Introduction: Adrenal incidentalomas are unexpectedly discovered adrenal masses with an estimated prevalence of 8%, often found during imaging for unrelated medical conditions. While primarily benign and hormonally inactive, these lesions have been associated with subtle cortisol autonomy, oxidative stress, and increased cardiovascular risk. The present study investigates the subclinical metabolic and cardiovascular impacts of non-functioning adrenal incidentalomas through oxidative stress and antioxidant marker analysis. Methods: This prospective study included 30 patients with non-functioning adrenal incidentalomas, compared to two control groups: 26 individuals with diabetes mellitus and/or hypertension (HT) and 24 healthy controls matched for age, sex, and body mass index. Hormonal evaluations, oxidative stress markers (malondialdehyde (MDA), nitric oxide (NO), and 3-nitrotyrosine (3-NTx)), antioxidant parameters (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), reduced glutathione (GSH), and melatonin), and high-sensitivity C-reactive protein (hsCRP) were assessed. Results: Oxidative stress markers were significantly elevated in patients with adrenal incidentalomas compared to controls (P < 0.001). Antioxidant markers, including SOD, CAT, GPx, GSH, and melatonin, were significantly lower in the case group (P < 0.001). Cortisol levels post-dexamethasone suppression, although within normal limits, were higher in the incidentaloma group, correlating positively with oxidative stress markers (MDA, NO, and 3-NTx) and inversely with antioxidant parameters. Elevated hsCRP levels in the case group indicated a pro-inflammatory state. Conclusions: Non-functioning adrenal incidentalomas are associated with heightened oxidative stress, diminished antioxidant capacity, and systemic inflammation, potentially contributing to cardiovascular and metabolic risks. These findings challenge the assumption that non-functioning incidentalomas are clinically insignificant, emphasizing the need for long-term monitoring and comprehensive evaluation of their systemic effects.